Analyzing the Theme of Loneliness and Oppression in The Yellow Wallpaper through Feminist Perspective - Aman, Maria; Siddiqui, Safia; Hafeez, Anum (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to explore the concept of feminism in The Yellow Wallpaper by Charlotte Perkins Gilman, a short story that explores the theme of loneliness and oppression of a woman through a feminist perspective. The study is qualitative in nature and uses textual analysis as an approach. The protagonist, a woman, is confined to her room and treated as an invalid by her husband, who is a doctor. She is not allowed to engage in activities that would stimulate her imagination and creativity, leading to feelings of isolation and loneliness. Through the protagonist's experience, Gilman critiques the patriarchal society of her time, where women were denied agency and considered inferior to men. In this story, all these things have been felt by the main character who has miraculous imagination. She found a painting and feel that there is a woman who has been strangled by the painting. She has crawled to get out of that painting but she failed. Indirectly she found herself in that woman who has been imprisoned in the painting. She is the living example of the oppressed creature in the clutches of patriarchal society. The yellow wallpaper in the story symbolizes the limitations imposed on the protagonist and other women of her time, highlighting the patriarchal control and oppression they face. In conclusion, The Yellow Wallpaper portrays the loneliness and isolation of women in a patriarchal society through a feminist lens.